Arbīṭ ou la purée d'herbes sauvages des Babors - Massinissa Garaoun (Revue d'ethnoécologie)
A survey looking at the different recipes of a mash made from wild grasses in the Babor Mountains in Algeria allowed us to study different linguistic phenomena related to the contact between Arabic and Berber in two of their varieties: the Jijelian Arabic (əž-Žīžlīya) and Berber Tasaḥlit (Ṯasaḥlit). We tried to broaden our field of study to describe that dish — and some comparable recipes attested among the Kabyle mountains —, to describe their places in these societies, and to question the collected linguistic data and their ethnolinguistic motivations, which led us to explore the fields of ethnobiology and culinary ethnology. Our results demonstrated the importance of the conservation of that dish for the transmission of knowledge related to local agroecosystems, in this area, which is experimenting an ever-increasing rural exodus.